A exposição do amor na internet: público ou íntimo? - MOREIRA, Jacqueline de Oliveira (Universidade Federal do Rio de Janeiro, 2023)
This article discusses the issue of intimacy and the publicization of love on the internet. It is based on a research which interviewed 20 university students of both genders to investigate if the internet introduces new forms of romantic relationships between adolescents. Inspired by the answers, this text proposes a theoretical reflection on the act of publicizing love online. Therefore, the effects of publicizing love life events on the internet are here discussed in two perspectives: analyzing the borders between public and private, and reflecting on the subjectivity involved in the publicization of our romantic lives. Although some interviewees criticize this exposure, some of them consider it a demand of contemporary culture. It could be noticed that, although the lack of conflicts caused by distance may give the illusion of the existence of a perfect relationship, the romantic bonds created by the internet can be as complex as the non-virtual relationships.